Relationship between Social Media Exposure and Adolescents’ Knowledge, Attitude and Behaviour to HIV/AIDS Prevention - Yusnita, Monica (JURNAL KOMUNIKASI INDONESIA, 2021)
This study was conducted to determine the relationship between the exposure level to HIV/AIDS information on social media and the knowledge level, attitude and behaviour in preventing the risk of HIV/AIDS transmission among adolescents. The research applieds a quantitative approach, survey techniques, descriptive statistical analysis and Partial-least Square Structural Equation Model (SEM) analysis. The samples in this study were 375 Bongas teenagers aged 13-24 years old who accessed the @sobat repro social media account. The results of the study show that most teenagers get high exposure to social media. Bongas teenagers have a good level of knowledge about HIV/AIDS and supportive attitude towards HIV/AIDS prevention. Most of the Bongas youths have positive HIV/AIDS prevention behaviours. Social media exposure has a significant effect on knowledge of HIV/AIDS. However, exposure to social media has no significant effect on attitudes and behaviour to prevent HIV/AIDS. Knowledge has a significant effect on attitudes and behaviour to prevent HIV/AIDS. Attitudes towards HIV/AIDS also have a significant effect on prevention behaviour. Social media exposure has a significant effect on knowledge-mediated prevention behaviour.